Ars erotica en die detrivialisering van die seksuele diskoers: "n Aantekening by die seksualiteitsanalise van Michel Foucault - Beukes, Johann (HTS teologiese studies, 2002)
Ars erotica and the detrivialization of the sexual discourse: An annotation to Michel Foucault’s analysis of sexualityThis essay is an attempt to detrivialize and depublicize the sexual discourse by reintroducing an aspect of Michel Foucault’s historiography of sexuality, namely his analysis of the intrinsic private nature of ars erotica, the classic notion of secretive eroticism. The article argues that sexuality has become an essentially public, objectifying and therefore oppressive discourse in modernity. By presenting the privatistic notion of ‘radical discretion’, it attempts to reclaim the deepest of ars erotica sentiments, namely the virtue of silence, in erotic contexts.